Diversity of the class II (I-Ak/I-Ek) restricted T-cell repertoire for influenza haemagglutinin and antigenic drift: six non-overlapping epitopes on the HA1 sub-unit are defined by synthetic peptides - MILLS, KINGSTON (The Rockefeller University Press, 1989)
H-2k-restricted T cell clones derived from CBA mice infected with X31 (H3N2) influenza virus, were shown to recognize distinct, nonoverlapping sequences within the HA1 subunit of the viral hemagglutinin (HA) using synthetic peptides. Three I-Ak-restricted T cell sequences were identified within HA1 68-83, 120-139, and 269-288, and two recognition sites presented in the context of the I-Ek molecule were mapped to HA1 sequences 226-245 and 246-265. T cell clones specific for these regions of HA1 demonstrated varying abilities to differentiate between natural variant viruses that had accumulated substitutions within their HA molecules as a result of antigenic drift. Clones that recognized sequences HA1 226-245 and HA1 246-265 failed to discriminate between natural variants and focused on conserved sequences within these epitopes. A majority of T cell clones were sensitive to amino acid substitutions that have featured in antigenic drift occurring within three major antigenic sites of the HA1 subunit; substitutions at HA1 residues 78 (V)/83(K) and 275(D)/278(I) within the HA1 subunit of mutant viruses correlated with a 75% reduction in the proliferative response for T cell clones specific for sequences HA1 68-83 and HA1 269-288, respectively. Furthermore, a clone that recognized HA1 120-139 was nonresponsive to a mutant virus HK/71, implicating amino acids at HA1 position 129(G) and/or 132(Q) within this sequence as crucial for recognition. Our data, together with the previous finding that sequence HA1 53-63 is also a major I-Ak-restricted T cell recognition site, demonstrate a level of diversity in the T cell recognition of influenza HA, within a single mouse haplotype hitherto unrecognized, and imply that the T cell repertoire diversity against foreign antigens may be greater than previously assumed. Furthermore, the frequency at which HA-specific T cells have been identified that focus on amino acids within the HA1 subunit of HA also featuring in antigenic drift, suggests that a failure of MHC class II-restricted T cells to recognize specific epitopes within mutant HA molecules may contribute significantly to the capacity of variant influenza viruses to evade immune recognition.
PUBLISHED
Keywords: Biochemistry